Results on Permutation Labeling of Graphs (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
A (p.q) -graph is said to be permutation graph if there exists a bijective function, f : V(G)--> {1,2,...p} In this paper, we investigate the permutation labeling for generalized prism and anti prism, grids, extended sun graph, necklace graph, special comb, comb, Mobius ladder and at the end a very general proof for permutation graphs.